2021
DOI: 10.1029/2020jd033959
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Propagation From Meteorological Drought to Hydrological Drought in the Pearl River Basin

Abstract: Due to global warming, extreme weather events occur more frequently. Compared with other natural hazards, drought is a slow-onset hazard that occurs in large areas over long time periods. Drought can have great impacts on socioeconomic development and ecological stability (King-Okumu et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 56 publications
(103 reference statements)
4
70
0
Order By: Relevance
“…As a result, the duration of hydrological drought is longer than that of meteorological drought, which explains why meteorological drought is intra-seasonal, while hydrological drought is interseasonal in the WRB. This conclusion is consistent with the ndings of literature review that meteorological droughts have a higher frequency and a shorter duration than those of hydrological droughts (Wu et al, 2017;Xu et al, 2019;Zhou et al, 2021). Consequently, according to the characteristics of meteorological and hydrological droughts in the WRB, corresponding measures (such as reservoir regulation, etc.)…”
Section: Intra-seasonal and Inter-seasonal Droughtssupporting
confidence: 89%
“…As a result, the duration of hydrological drought is longer than that of meteorological drought, which explains why meteorological drought is intra-seasonal, while hydrological drought is interseasonal in the WRB. This conclusion is consistent with the ndings of literature review that meteorological droughts have a higher frequency and a shorter duration than those of hydrological droughts (Wu et al, 2017;Xu et al, 2019;Zhou et al, 2021). Consequently, according to the characteristics of meteorological and hydrological droughts in the WRB, corresponding measures (such as reservoir regulation, etc.)…”
Section: Intra-seasonal and Inter-seasonal Droughtssupporting
confidence: 89%
“…The average annual runoff of each sub-region is 775, 433, 1,410, 799, and 852 mm, and the variation of runoff in each sub-region is 7. 47, 6.74,13.75, 7.19, and 10.54 mm/a, respectively (Zhou, Shi, et al, 2021). The land use in the study area is shown in Figure 1c, which mainly includes croplands (CR), woody savannas, mixed ZHOU ET AL.…”
Section: Study Areamentioning
confidence: 99%
“…The average annual precipitation of each sub‐region is 1,828, 1,353, 2,371, 1,679, and 1,847 mm, and the variation of precipitation in each sub‐region is 6.14, 5.93, 12.91, 5.79, and 9.77 mm/a, respectively. The average annual runoff of each sub‐region is 775, 433, 1,410, 799, and 852 mm, and the variation of runoff in each sub‐region is 7.47, 6.74,13.75, 7.19, and 10.54 mm/a, respectively (Zhou, Shi, et al., 2021). The land use in the study area is shown in Figure 1c, which mainly includes croplands (CR), woody savannas, mixed forests (MF), and evergreen broadleaf forest (EBF).…”
Section: Study Area and Datamentioning
confidence: 99%
“…In other words, the river flow cannot satisfy the water supply demand in a certain period (Van Loon & Van Lanen 2012;Van Loon & Laaha 2015). According to the definition of hydrological droughts and Karst basin characteristics (Tsakiris et al 2007;Liu et al 2012;LĂłpez-Moreno et al 2013;Jehanzaib et al 2020;Zhou et al 2020), the SRI was quoted to describe the hydrological drought characteristics in this paper. The SRI can be expressed as follows:…”
Section: Identification Of Hydrological Droughtmentioning
confidence: 99%